Comparison between Performance of Okra Waste and Wheat Bran for Removing some Heavy Metals from Wastewater - Esgair, Karim Khalifa (Al-Nahrain Journal for Engineering Sciences, 2018)
In the present work, the agricultural wastes which are wheat bran and raw okra waste used as adsorbent material for adsorption of cadmium and copper ions from wastewater .The effect of adsorption variable which include initial pH of solution , agitation speed, agitation time, initial concentration of cadmium and copper ions, and amount of adsorbent material were investigated in a batch process in order to obtain the maximum ions removal from wastewater .The results obtained from experimental investigation show that the percentage removal of metal ions increases with increasing pH and agitation speed until a maximize value after that it decreased with increasing pH and agitation speed. Also increases with increasing amount of adsorbent material and agitation time until a maximize value then reach a constant value approximately , and decreasing with increasing metal ions concentration .The maximum removal percent of cadmium and copper ions were 85.8% and 52.7 % respectively which obtained at pH equal 5.0, agitation speed 150 revolution per minute, agitation time 105 minute , metal ion concentration 40mg /L ,and adsorbent amount 1.5gm when using wheat bran as adsorbent material ,while obtained the maximum removal percent of cadmium and copper ions were 81.7% and 47.8 % which obtained at pH equal 6.0, and pH equal 5.0 respectively , agitation speed 150 revolution per minute, agitation time 90 minute ,metal ion concentration 40 mg /L ,and adsorbent amount 1.5gm when using okra waste as adsorbent material. From above result the wheat bran and okra waste was a best adsorbent material for removal cadmium and copper ions from wastewater but wheat bran slightly more effective than okra waste._x000D_